Tradisi Ziarah Kubro Masyarakat Kota Palembang dalam Perspektif Hierarki Nilai Max Scheler - Prima Amri; Septiana Dwiputri Maharani (Jurnal Filsafat "WISDOM", 2018)
The background of this article is the local wisdom of people of Palembang city, in the form of a tradition called Ziarah Kubro (The Great Pilgrimage) which actually contains philosophical values but in practice it is still understood as merely a ritual. This article aims to analyze the Ziarah Kubro tradition employing perspective of Max Scheler’s hierarchy of values. This article provides indepth analysis regarding the values contained in the tradition of Ziarah Kubro using descriptive analytics as a form of literature review. Results of the study suggest that Ziarah Kubro tradition contains philosophical values, namely the value of pleasure, vitality, spirituality, and religius. Based on Max Scheler hierarchical perspective, religius values are the highest values upheld by the people of Palembang City. These values can be sensed through preferences influenced by the feelings of love and hate. This preference has implications towards the attitudes of the Palembang people who always carry out and preserve this tradition to the next generation in the hope of attaining blessings and increasing religious life in society.